Smart Financial Future: Education on Sharia Financial Planning for Students - Mifta Hasda; Muhammad Syaipudin; Hidayat Hidayat (Global Sustainability Research Institute, 2025)
Financial literacy is an essential competency that young people need to face increasingly complex economic challenges. However, many high school students still lack adequate understanding of financial planning and management, particularly from an Islamic perspective. This community service program aimed to enhance students’ understanding of Islamic financial planning as a foundation for achieving future financial independence. The program employed a participatory educational approach consisting of interactive lectures, discussions, question-and-answer sessions, and simple budgeting simulations. The materials covered Islamic financial literacy, money management, budgeting, saving habits, consumer behavior control, and the application of Islamic values in financial decision-making. The results indicated that participants demonstrated improved understanding of financial planning, the ability to distinguish between needs and wants, and greater awareness of managing finances wisely in accordance with Islamic principles. Furthermore, the program enhanced students’ awareness of ethical values and social responsibility in economic activities. Therefore, Islamic financial planning education can serve as an effective tool for improving youth financial literacy and fostering healthy and sustainable financial behavior.